Experimental study of cutting parameter for drilling on fabric carbon/epoxy composite laminates - Abd Halim, Nor Farah Huda; -, Afzeri; Aminanda, Yulfian (Trans Tech Publications Ltd, 2011)
This study is mainly about the drilling of carbon-epoxy laminates. Variation of cutting parameter such as feed rate (50,100 and 150 mm/min) and speed(400,800,1200 rpm) were tested in this study. 6 different laminates orientation (0°/0°/0°/0°, 45°/45°/45°/45°, 0°/45°/0°/45°, 45°/0°/45°/0°, 0°/0°/45°/45° and 45°/45°/0°/0°) were tested in order to see which one is the best. HSS twist drill with 4mm diameter was use in this study. The damage of the composites was seen under digital microscope. The aim of this study is to find the minimum force and the minimum damage mechanism i.e.: entry and exit delamination. The drilling process with different parameter of cutting and the orientation were carried out in order to see the influenced of this parameter to the force and the damage mechanism. The general factorial was used to randomise the number of experiment.